2011
DOI: 10.3945/jn.111.147520
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Bolus Feeding Has a Greater Stimulatory Effect on Protein Synthesis in Skeletal Muscle Than Continuous Feeding in Neonatal Pigs

Abstract: Orogastric tube feeding, using either continuous or intermittent bolus delivery, is common in infants for whom normal feeding is contraindicated. To compare the impact of different feeding strategies on muscle protein synthesis, after withholding food overnight, neonatal pigs received a complete formula orally as a bolus feed every 4 h or were continuously fed. Protein synthesis rate and translational mechanisms in skeletal muscle were examined after 0, 24, and 25.5 h. Plasma amino acid and insulin concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
84
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 45 publications
8
84
3
Order By: Relevance
“…This is consistent with the lack of effect of leucine pulses on the abundance of ribosomal protein S4 and S8 mRNA in polysomes, suggesting that leucine pulses may not stimulate ribosomal biogenesis. Although intermittent bolus feeding increases the aggregation of ribosomes on mRNA in skeletal muscle more than continuous feeding (40), in this study we could not detect an effect of leucine pulses on the proportion of ribosomes in polysomes. …”
Section: E707 Leucine Pulses Increase Lean Gain In Neonatescontrasting
confidence: 42%
See 3 more Smart Citations
“…This is consistent with the lack of effect of leucine pulses on the abundance of ribosomal protein S4 and S8 mRNA in polysomes, suggesting that leucine pulses may not stimulate ribosomal biogenesis. Although intermittent bolus feeding increases the aggregation of ribosomes on mRNA in skeletal muscle more than continuous feeding (40), in this study we could not detect an effect of leucine pulses on the proportion of ribosomes in polysomes. …”
Section: E707 Leucine Pulses Increase Lean Gain In Neonatescontrasting
confidence: 42%
“…Recent findings in our neonatal piglet model have demonstrated that continuous feeding by orogastric tube reduces protein synthesis and blunts protein deposition compared with intermittent bolus feeding for 24 h (31,32,40). This reduced response to the same nutrient load is due to the relatively suppressed and constant hormone and substrate patterns incurred with continuous feeding that attenuate muscle protein synthesis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although intermittent bolus feeding has been advocated because it is more physiological, as it mimics the hormonal profile of meal feeding, continuous feeding is still indicated for some patients due to feeding intolerance (20,58). Recently, we demonstrated, using neonatal pigs as a model for the human neonate, that orogastric continuous feeding blunts protein synthesis in skeletal muscle compared with intermittent bolus feeding (26,32).…”
mentioning
confidence: 99%